DESENTRALISASI FISKAL KONTEMPORER DALAM PERSPEKTIF KEBIJAKAN PUBLIK ISLAM - Setianingrum, Any (Faculty of Economics and Business, University of Muhammadiyah Malang, 2013)
One of the essential instruments designed for achieving the goals of sharia in Islam is fiscal policy. There are some key elements of Islamic fiscal theory, namely: 1) Islamic Economics, which comprises private sector, social/ voluntary sector, and public sector. The collaboration of these three sectors would provide an ideal Islamic economic institutional framework; 2) Zakat (taxation of income and wealth of a Muslim) as the basis of fiscal system; 3) Implementation of all fiscal instruments which disallow exploitation that results in usury (riba), uncertainty (gharar ), speculation, sinful (haram) products / services and all forms of meanness. 4) Allocation, distribution and stabilization functions of Islamic economics is administered and presented through all the sectors cooperatively; 5) Public sector does not affect significantly yet essential on condition that it works continuously to ensure optimum allocation of society resources, income distribution, and stability establishing